Vulkan-Sim: A GPU Architecture Simulator for Ray Tracing - Saed, Mohammadreza; Chou, Yuan Hsi; Liu, Lufei; Nowicki, Tyler; Aamodt, Tor M. (2022 55th IEEE/ACM International Symposium on Microarchitecture (MICRO), 2022)
Ray tracing can generate photorealistic images with more convincing visual effects compared to rasterization. Recent hardware advances have enabled ray tracing to be applied in real-time. Current GPUs feature a dedicated ray tracing acceleration unit, and game developers have started to make use of ray tracing APIs to bring more realistic graphics to their players. Industry cooperatively contributed to Vulkan, which recently introduced an open-standard API for ray tracing. However, little has been disclosed about the mapping of this API to hardware. In this paper, we introduce Vulkan-Sim, a detailed cycle-level simulator for enabling architecture research for ray tracing. We extend GPGPU-Sim, integrating it with Mesa, an open-source graphics library to support the Vulkan API, and add dedicated ray traversal and intersection units. We also demonstrate an explicit mapping of the Vulkan ray tracing pipeline to a modern GPU using a technique we call delayed intersection and any-hit execution. Additionally we evaluate several ray tracing workloads with Vulkan-Sim, identifying bottlenecks and inefficiencies of the ray tracing hardware we model. To demonstrate the utility of Vulkan-Sim we conduct two case studies evaluating techniques recently proposed or deployed by industry targeting enhanced ray tracing performance.